Construction of five zinc coordination polymers with 4-substituted bis(trizole) and multicarboxylate ligands: Syntheses, structures and properties. (15th November 2018) - Zhang, Ya-Qian; Blatov, Vladislav A.; Lv, Xiu-Xiu; Yang, Chang-Hao; Qian, Lin-Lu; Li, Ke; Li, Bao-Long; Wu, Bing
Graphical abstract: Five zinc coordination polymers were synthesized and characterized.1 is a high sensitive and selective luminescence sensor for detection of Cr2 O7 2−, CrO4 2− and Fe 3+ in aqueous solution. Abstract: Five zinc coordination polymers {[Zn2 (mtrb)2 (btec)]·H2 O} n (1 ), {[Zn(mtrb)(Meip)]·H2 O} n (2 ), [Zn(mtrb)(nip)] n (3 ), {[Zn(mtrb)(hip)]·H2 O} n (4 ) and [Zn(mtrb)(nbdc)] n (5 ) (mtrb = 1, 3-bis(1, 2, 4-triazol-4-ylmethyl)benzene, btec = 1, 2, 4, 5-benzenetetracarboxylate, Meip = 5-methylisophthalate, nip = 5-nitroisophthalate, hip = 5-hydroxyisophthalate, nbdc = 4-nitro-1, 2-benzenedicarboxylate) were synthesized and characterized.1 shows a (4, 4)-connected self-catenated 3D network with a point symbol of {6 2 .8 4 }{6 4 .8 2 }2, which belongs to the 4, 4T32 topological type.2 is a 1D chain structure containing [Zn(mtrb)(Meip)] 20-membered cycle.3 is a 1D chain structure containing [Zn(nip)2 ] 16-membered cycle and [Zn(mtrb)2 ] 24-membered cycle.4 and5 exhibit the undulated 2D (4, 4) network.1 is a highly sensitive and selective luminescence sensor for detection of Cr2 O7 2−, CrO4 2− and Fe 3+ in the aqueous solution. The detection limits for Cr2 O7 2−, CrO4 2− and Fe 3+ are 3.05 μM, 5.72 μM, and 6.28 μM, respectively. The luminescence sensor is stable and can be recycled for detection at least five times. The possible quenching mechanisms were discussed.